Masterworks of the Orchestral Repertoire : a Guide for Listeners. - Ferguson, Donald N. (University of Minnesota Press, 1954)
The fullest enjoyment of an orchestral performance or a record concert comes with a background of knowledge about the music itself. This handbook is designed to help music lovers get the ultimate pleasure from their listening by providing them with that b.